(untitled) (Prosiding Seminar Nasional Matematika dan Pendidikan Matematika, 2025)
Students’ ability to understand mathematical concepts in Indonesia still tends to be low. Students’ ability to understand mathematical concepts is used as a basis for students to understand subsequent materials that are related to each other. There is a need for innovation that can help improve these abilities, one of which is the game-based learning model. This research aims to describe a game-based learning model to improve the ability to understand concepts in terms of self-concept. The research method used is a literature study that analyzes various sources related to the topic. The data analysis technique consists of four stages, namely data collection, data reduction, data display, and conclusion drawing/verification. The study results show that the game-based learning model positively affects students’ ability to understand mathematical concepts, so it can be an interactive learning innovation to improve this ability. Apart from that, self-concept also has a positive influence on students’ ability to understand mathematical concepts. Further research needs to be carried out to determine students’ ability to understand mathematical concepts, which are reviewed using self-concept and a game-based learning model directly implemented with students.